Occlusal caries risk assessment using Cariogram analysis in student aged 11-12 years - Wardani, Riana; Zubaedah, Cucu; Setiawan, Asty Samiaty (Padjadjaran Journal of Dentistry, 2017)
ABSTRACTÂ Introduction: Basic Health Research 2013 showed Dental Caries Index in school age student in West Java was lower than the expected target, with occlusal surface as most affected part. The purpose of this study was to determine the risk status of dental caries in school age student by using cariogram analysis. Methods: Observational research. Study was conducted on 30 student aged 11-12 years with caries high risk on occlusal surfaces. Purposive sampling was taken from students of SDN Cikawari and SDN Mekarjaya Bandung Regency with high DMF-S index. Inclusion criteria: male and female, aged 11-12 years, good systemic health, SDN Mekarjaya and SDN Cikawari Bandung Regency students. Exclusion criteria: suffering from systemic disorder, currently in long-term antibiotic therapy, orthodontic appliance usage. Case history, eating habits and intake of fluoride, caries experience, salivary volume and buffering capacity of each sample was examined using cariogram examination method. Results: The cariogram analysis showed 43% chance of caries avoidance. Diet control was 23.3%, includes two factors: sugary foods and eating frequency. Bacteria control was 11.9% by evaluating both bacterial factors (the amount of plaque and the bacteria Streptococcus mutans). Vulnerability control was 14.4%, including caries prevention by the continuation of fluorine program and other conditions control that affect salivary secretions.Â Conclusion: Based on cariogram analysis found that all samples who had occlusal surfaces caries were at a high risk category, but still having moderate potential of avoiding new caries occurrence by controlling risk factors.Keywords: Cariogram analysis, Occlusal caries, Aged 11-12 years